Ferroelectric polarization and iron substitution synergistically boost electrocatalytic oxygen evolution reaction in bismuth oxychloride nanosheets - Singh, Dinesh; Joshi, Bhavana; Poddar, Pankaj (Langmuir, 2023)
Ferroelectric materials have gained significant interestin variouskinds of water splitting, but the study of ferroelectric materialsfor electrocatalytic water splitting is in its infancy. Ferroelectricmaterials have spontaneous polarization below their Curie temperaturedue to dipolar alignment, which results in surface charges. In 2Dferroelectric materials, spontaneous polarization depends on thickness.Herein, we report that thickness-dependent ferroelectric polarizationin 2D nanosheets can also accelerate the oxygen evolution reaction(OER) along with the tailored active surface area of exposed crystallinefacets, which improves the electrocatalytic activity relatively. Iron-substitutedBiOCl nanosheets of varying thickness are fabricated by varying thepH using a facile coprecipitation method. The substituted iron enhancespolarization and electrochemical active sites on the surface. Thefindings in this study show that the exposed (001) facet and higherthickness of the nanosheets have high ferroelectric polarization and,in turn, superior electrocatalytic activity and remarkable stability,requiring low overpotentials (348 mV and 270 mV at 100 mA/cm(2) and 10 mA/cm(2)) in alkaline (1.0 M KOH) electrolyte. Asthe thickness of the nanosheets is decreased from 140 to 34 nm, theelectrocatalytic performance of iron-substituted BiOCl nanosheetsstarts to reduce due to the lower Coulomb-Coulomb interactionand the increasing depolarization.